2017
DOI: 10.12693/aphyspola.131.576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yttria on the Phase Formation and Sintering of HA-Al2O3Biocomposites

Abstract: Hydroxyapatite is very-well known as the main component of hard tissues and, as such, it has attracted much attention by researchers in the recent decades. This study was aimed to present the characterization of Y2O3 doped 50 wt.% hydroxyapatite -50 wt.% Al2O3 composite materials fabricated at relatively high temperature of 1600• C. Hydroxyapatite powder was obtained from bovine bones via calcination and ball milling technique. Fine powders (≤ 1 µm) of hydroxyapatite/Al2O3 were admixed with 0.5 and 1 wt.% Y2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although Al2O3 is highly biocompatible and wear-resistant, it possesses low flexural strength and toughness (Marti, 2000). In order to enhance its mechanical properties, two composite materials have been developed by incorporating a second phase (Jang et al, 1995;Öksüz and Özer, 2017) or embedding whisker (Tan et al, 2020) into an Al2O3 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Although Al2O3 is highly biocompatible and wear-resistant, it possesses low flexural strength and toughness (Marti, 2000). In order to enhance its mechanical properties, two composite materials have been developed by incorporating a second phase (Jang et al, 1995;Öksüz and Özer, 2017) or embedding whisker (Tan et al, 2020) into an Al2O3 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have indicated that hydroxyapatite is biocompatible with hard tissues of human beings and exhibits osteoconductive properties [3]. Thus, it is considered as the most promising bioactive material for clinical use [4][5][6]. However, despite its good biocompatibility and bioactivity, the low mechanical strength of hydroxyapatite restricts its applications for small and low load bearing implants and/or surface-coating of different im-plant materials [7][8].…”
Section: Introductionmentioning
confidence: 99%